Legal education in Burma since the 1960s : A personalized update and account - Myint, Zan (Universiti Malaysia Sarawak, UNIMAS, 2006)
In January 1962 issue of International and Comparative Law Quaterly the late Dr. Maung Maung (31 January 1925 – 2 July 1994) wrote a short note and comment in the Comments Section of the Journal entitled ‘Lawyers and Legal Education in Burma’. Since then much water has passed under the bridge in the field of legal education in Burma and to the best of this author’s knowledge there has never been an update in academic legal journals or in books about this subject. This article is intended to fill this lacuna in considerable detail and also to comment on variegated aspects of legal education in Burma since the 1960s.